2022
DOI: 10.20944/preprints202201.0150.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral Hygiene Practices and Knowledge among Adolescents Aged between 15 and 17 Years Old during Fixed Orthodontic Treatment: Multicentre Study Conducted in France

Abstract: The aims of this study were to assess oral health knowledge, attitudes, and practices among orthodontic patients between the ages of 15 and 17 years old compared to adolescents without orthodontic treatment. This cross-sectional study included 392 adolescents drawn from various French teaching hospitals. A closed-ended questionnaire was used to collect data. Adolescents undergoing orthodontic treatment had a higher knowledge of oral health than adolescents without orthodontic treatment. The majority of adolesc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…51 However, research has found that orthodontic patients tend to have greater knowledge about using various oral hygiene appliances. 52 Our hypothesis is that due to the heightened risk of oral health issues, 53 orthodontic patients receive close monitoring, education and encouragement to maintain high levels of dental hygiene and thus continue to prioritise their dental hygiene after treatment.…”
Section: Tmds and Orthodontic Treatmentmentioning
confidence: 99%
“…51 However, research has found that orthodontic patients tend to have greater knowledge about using various oral hygiene appliances. 52 Our hypothesis is that due to the heightened risk of oral health issues, 53 orthodontic patients receive close monitoring, education and encouragement to maintain high levels of dental hygiene and thus continue to prioritise their dental hygiene after treatment.…”
Section: Tmds and Orthodontic Treatmentmentioning
confidence: 99%